Physicochemical, Microbiological and Sensory Properties of Fermented Whey using Kombucha Inoculum - Fitri Suciati; Nurliyani Nurliyani; Indratiningsih Indratiningsih (Buletin Peternakan, 2019)
This research aimed to determine physicochemical, microbiological and sensory properties of fermented whey using kombucha inoculum. The material used were kombucha, black tea, green tea, and whey protein concentrate. The research used factorial completely randomized design. The first factor was kombucha inoculum using different mediums (black and green tea) at different levels (5; 10; 15; dan 20%) as a second factor. The whey was fermented at 37oC for 39 hours. Research showed the use of kombucha inoculum using different medium (black and green tea) at different levels (5; 10; 15; dan 20%) did not affect (p>0.05) on microbiological properties (the number of Total Plate Count, total lactic acid bacteria, total acetic acid bacteria, and total yeast), dissolved protein content, lactose content, viscosity and acceptability. Black and green tea kombucha inoculum can be used in whey fermentation. Black tea kombucha fermented whey with 20% level addition has the best solid content. Relatively, kombucha fermented whey is quite acceptable.